PERAN TUHAN DALAM RITUAL PERKAWINAN ADAT GUYUB TUTUR MANGGARAI: KAJIAN LINGUISTIK KEBUDAYAAN - Yohanes P.F Erfiani; Maria Goretti Djehatu; Simforianus Mario Bajo (Lingua: Jurnal Bahasa, Sastra dan Pengajarannya)
This research article is conducted to find out the God’s role which contained in the traditional marriage discourse of Manggarai speech community. In other words, this article is intended to describe and narrate the God’s role in Manggarai culture, especially in the traditional marriage ritual. Therefore, this research article applied cultural linguistic perspective which is proposed by Gary B. Palmer as the theory for analyzing the God’s role in traditional marriage discourse of Manggarai speech community. The cultural linguistic theory is combined with the qualitative research method. Moreover, this research article is conducted in Cibal district, Manggarai regency, East Nusa Tenggara province. Thus, based on the source of the data, it can be concluded that God has the important role in conducting traditional marriage ritual of Manggarai speech community. Several roles which revealed in traditional marriage ritual of Manggarai speech community is God is believed to be the highest being, God is believed to be the creator of the universe/world, God is believed to be a guide, protector, and grantor of wishes, and God is believed to have the same appearances as humans.